Numerical Soliton Solutions for a Discrete Sine-Gordon System (Communications in Computational Physics, 2009)
In this paper we use an analytical-numerical approach to find, in a systematicway, new 1-soliton solutions for a discrete sine-Gordon system in one spatial dimension.Since the spatial domain is unbounded, the numerical scheme employed togenerate these soliton solutions is based on the artificial boundary method. A large selectionof numerical examples provides much insight into the possible shapes of thesenew 1-solitons.